Information System of Muara Badak Village Culinary Sales Using Laravel Web-Based - Trikoyat; Yulianto; Eny Maria (Politeknik Pertanian Negeri Samarinda, 2022)
The world of technology is developing very fast. In line with this, the fast-growing business growth and development is driven by various supporting factors including promotions and advertising boards. As one of the villages, Muara Badak Village has many tourist attractions to visit this village. One of the biggest attractions is the culinary field and beach tourism, so there are so many culinary places that are very diverse. Therefore, the purpose of this research is to utilize existing knowledge in college to build an application, namely information media that provides sales services through culinary applications by looking at newcomers and tourists who do not understand the culinary specialties of Muara Rhino Village and view an environment that can be free. from the Covid-19virus through online buying and selling so researchers are trying to make the application. The results of this study are the birth of an application called MB FOOD not only to take advantage of the application but how to make a bridge between consumers and sellers to make it easier to connect people around, by looking at problems and technological developments now how to find ideas that are useful for the community. It is hoped that this research can be used as a reference for the next time and the progress of future technological developments by looking at people's current income so that the government can see people's income and participate in developing the MB FOOD application to help each other and learn together further technological developments.